PENGARUH FAKTOR INDIVIDUAL, FAKTOR LINGKUNGAN DAN STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PAKAIAN DENGAN POTONGAN HARGA, DI GERAI MATAHARI LOMBOK EPICENTRUM MALL MATARAM - ARTIKA, IDA BAGUS EKA; ARIFIANTI, INDAH; KENCANA, A. A. MADE SURYA; MARINI, IDA AYU KETUT (Universitas Mahasaraswati Mataram, 2020)
This study aims to determine the influence of individuals, the environment and marketing strategies in consumer decision making in buying clothing products at discounted prices at Matahari Department Store outlets, Lombok Epicentrum Mataram. The type of research is associative with the data collection method is survey sample. The sampling technique was purposive sampling with 40 respondents and the data were analyzed multiple regressionsThe results showed that there was a positive and significant partial influence of individual variables and marketing strategies on the decision to buy clothes at a discount at the Matahari Lombok Epicentrum Mall Mataram outlet, while environmental variables did not significantly influence, simultaneously the three variables had a significant effect, individual variables, environment. and marketing strategies contributed or played a role in influencing purchasing decisions by 34.3% and 65.7% were influenced by other factors.The individual factor is the dominant variable in influencing consumers in deciding to buy clothes at a discount at Matahari Lombok Epicentrum Mall Mataram outlets.